ANALYSIS OF THE EFFECT OF BOARD DIVERSITY ON BANKING FIRM PERFORMANCE IN INDONESIA - Andre Christian Setiohandiko; Werner Ria Murhadi (Jurnal Media Ekonomi (JURMEK), 2026)
Purpose: This study aims to analyze the effect of board of directors' diversity — across three dimensions (gender, age, and nationality) — on the performance of Indonesian banking firms, measured through four performance proxies (ROA, Tobin's Q, CAR, and NPL). Research Methodology: Panel data from 44 banks listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period (220 firm-year observations) were analyzed using panel data regression, with model selection conducted through the Chow test and the Hausman test; all data processing was performed using EViews. Results: Nationality diversity has a significant positive effect on ROA and CAR; age diversity (the proportion of directors aged below 54 years) has a positive effect on Tobin's Q and CAR but a negative effect on ROA; gender diversity does not show a significant effect on any of the performance proxies; and the model for NPL is not simultaneously significant, so the results related to credit risk cannot be conclusively determined. Conclusions: Nationality diversity is the most strategic dimension for enhancing bank performance, whereas the benefits of gender diversity have not yet been optimally realized due to its still-low representation on Indonesian bank boards. Limitations: This study does not include control variables such as bank size, bank age, past profitability, or the COVID-19 pandemic period, which caused the NPL model to be simultaneously insignificant. Contributions: This study addresses the gap left by prior research, which has tested board diversity dimensions only partially and separately; its novelty lies in simultaneously examining three diversity dimensions (gender, age, and nationality) against four performance proxies (ROA, Tobin's Q, CAR, and NPL) within a single empirical model for Indonesian banking firms. Theoretically, this study extends Resource Dependence Theory to a developing-country banking context by showing that board capital is contingent on institutional context and representation thresholds; practically, it offers implications for bank management in structuring board composition, for regulators (OJK) in formulating governance policy, and for investors in assessing the prospects of banking issuers.